Increasing persistence : research-based strategies for college student success - Habley, Wesley R.; Bloom, Jennifer L.; Robbins, Steven B. (USA Jossey Bass, 2012)
"This groundbreaking book offers a compendium on college student persistence that bridges the gap between concept, theory, and research to successful practice. The book is anchored by the American College Testing organization's What Works in Student Retention survey of 1,100 colleges and universities, which provides insights on the causes of attrition and identifies retention interventions most likely to enhance student persistence. It also includes decision-makers and practitioners with evidence-based interventions and best practices for improving student persistence"--
Keywords: College dropouts -- United States -- Prevention; EDUCATION / Higher